Metaevaluation as a Means of Examining Evaluation Influence - Monica LaBelle Oliver (The Evaluation Center at Western Michigan University, 2009)
Understanding how (or whether) an organization uses its evaluation findings can help that organization and others like it to evaluate more purposefully and effectively. Understanding the broader influence evaluations have on the organization and in its operating environment holds even greater potential. Metaevaluation is an appropriate approach for determining how effectively evaluations have served the purpose of program improvement. They can potentially expose other intended or unintended ways in which the evaluation influenced the organization and its environs. Using Henry and Mark's (2003) taxonomy of evaluation influence as a platform for classification and analysis, this study metaevaluates one organization's evaluations with an eye toward how those evaluations influenced it, whether through program improvement or other means. Metaevaluation proves a valuable means of exposing subtle forms of influence in the organization, as well as a way of revealing how it might evaluate in the future with an eye toward having even greater intentional influence.